Kick shop Malaya / Muhammad Adlan Abdul Jamil - Abdul Jamil, Muhammad Adlan (2018)
Kickshop Malaya is a business that carries out online business for sneakers shoes. Kickshop Malaya product consist different type of vans shoes.This business is created to provide an opportunity to all customers who love sneakers shoes and want to have them at affordable price. Apart from selling products to consumer, Kick shop Malaya Perfume also provides useful tips and info to our lovely customer. Retaining Kick Shop Malaya's customers is a very strong suit for this business and so we have strategies in place to ensure that our customers remain happy with our products and services. This can be achieved if we employ the best customer services executives who are adept at handling orders, promptly attending to complaints and inquiries. We also intend to provide a listening ear to our clients for feedback that will help make the company progress. In addition to reinforcing strategies for maintain customer loyalty toward Kick Shop Malaya's, expanding and exploring ways to promote this online product and services business in social media is important. Skills and ways to know how to attract customers are important. Start by giving teaser a customer to give the customer a sense of excitement to know which product to sell. Next, the skills to make soft sell to give you an idea of exactly what the product is going to sell in the right way. Last but not least, hard-sell-making skills to customers to attract customers continue to buy promoted products.